Comparison of the San Francisco Syncope Rule, Canadian Syncope Risk Score and Anatolian Syncope Rule in Patients Presenting to the Emergency Department with Syncope - Doğan, Burcu; Komut, Seval; Sultanoğlu, Hasan; Duran, Cemal Yasin; Yazla, Merve; Günsay, Rabia Handan (The European Research Journal, 2026)
Objectives: Syncope is a common cause of emergency department admissions and poses challenges in patient management due to its broad etiology and risk of short-term adverse events. This study aimed to comparatively evaluate the ability of the San Francisco Syncope Rule, Canadian Syncope Risk Score and Anatolian Syncope Rule to predict short-term (1-week and 1-month) adverse events in patients presenting to the emergency department with syncope. Methods: This multicenter, prospective, observational study included 108 patients who presented to the emergency departments of two tertiary-level hospitals with syncope. Patients aged